Bridging Organization Design and Performance : Five Ways to Activate a Global Operation Model. - Kesler, Gregory (Wiley, 2015)
Of the ChapterChapter 9: Design Process for Activation; Set a Road Map with a Realistic View of the Timeframe; Build Leadership Alignment into the Plan; Management Summit Meetings; Establish the Right Project Infrastructure; Work the Intersections in the New Organization; Measure Progress and Make Course Corrections; Summary of the Chapter; Chapter 10: When the Activators Work Together; Across the Five Activators; The Right Connections; The Right Conversations; The Right Know-How; Chapter 11: The Organization Health-Check Tool Kit; Bibliography; About the Authors; Amy Kates.